Characterization of individual stacking faults in a wurtzite GaAs nanowire by nanobeam X‐ray diffraction. (9th August 2017) - Davtyan, Arman; Lehmann, Sebastian; Kriegner, Dominik; Zamani, Reza R.; Dick, Kimberly A.; Bahrami, Danial; Al-Hassan, Ali; Leake, Steven J.; Pietsch, Ullrich; Holý, Václav
Abstract : The application of the synchrotron‐radiation‐based coherent nanobeam X‐ray diffraction method to study the type, quantity and the exact distances in between stacking faults in single GaAs nanowires is demonstrated. Abstract : Coherent X‐ray diffraction was used to measure the type, quantity and the relative distances between stacking faults along the growth direction of two individual wurtzite GaAs nanowires grown by metalorganic vapour epitaxy. The presented approach is based on the general property of the Patterson function, which is the autocorrelation of the electron density as well as the Fourier transformation of the diffracted intensity distribution of an object. Partial Patterson functions were extracted from the diffracted intensity measured along the direction in the vicinity of the wurtzite Bragg peak. The maxima of the Patterson function encode both the distances between the fault planes and the type of the fault planes with the sensitivity of a single atomic bilayer. The positions of the fault planes are deduced from the positions and shapes of the maxima of the Patterson function and they are in excellent agreement with the positions found with transmission electron microscopy of the same nanowire.